DAKWAH WASATHIYYAH BAGI GENERASI MILENIAL PERSPEKTIF AL-QUR’AN - Nurrochim, Zuni (AT-TAISIR: Journal of Indonesian Tafsir Studies, 2023)
This article examines the concept and implementation of wasathiyyah da'wah for the millennial generation from the perspective of the Qur'an. Wasathiyyah da'wah is explained as an effort to invite people to the teachings of Islam by emphasizing the principle of balance and moderation in thought, speech, and action. This research is qualitative research using primary and secondary data. In addition, this research also uses the thematic interpretation method to analyze the verses of the Qur'an that are relevant to the theme of da'wah. The author finds that wasathiyyah da'wah is da'wah that is based on balance, moderation, and mercy for the universe. Wasathiyyah da'wah also has concepts and characteristics that are suitable for the character and needs of the millennial generation, such as creative, innovative, to the point, friendly, up to date, fun, and interactive. This article contributes to understanding the principles of wasathiyyah da'wah that are relevant to guide the millennial generation in facing the challenges of the modern era.